PEMBANGUNAN OLAHRAGA KOTA SELONG KABUPATEN LOMBOK TIMUR DITINJAU DARI SPORT DEVELOPMENT INDEX - Daniyantara, Didik -; Suryansah, Suryansah (Universitas Hamzanwadi, 2018)
This study aims to examine the availability of sports open space, and the level of community participation in sports in Selong City, East Lombok Regency. Research is a quantitative descriptive research where the results obtained are obtained through research instruments in the form of observations to obtain data on the availability of land or open space for exercise, questionnaires/ questionnaires to obtain data on the level of community participation in sports activities. From the research conducted, results have been obtained that the development of sports in the city of Selong is still relatively low, this can be seen from the results of the City Selong sports development concluded as follows: 1) The open space index value is 0.411, this value when viewed from the SDI norm is in the low category , meaning that the availability of open space for sports in the city of Selong is not yet sufficiently available. 2). The Participation index value is 0.332, based on SDI norms it is still in the low category, meaning that the level of community participation in exercise is still low. from the index value, it is obtained that the Selong City sports development index value is 0.302, this value if viewed from the SDI norm is in the range of 0,000-0,499, meaning that the development of the sport in the city of Selong is still in the low category